Mixed Chroma Sampling-Rate High Efficiency Video Coding for Full-Chroma Screen Content - Lin, Tao; Zhang, Peijun; Wang, Shuhui; Zhou, Kailun; Chen, Xianyi (IEEE transactions on circuits and systems for video technology, 2013)
Computer screens contain discontinuous-tone content and continuous-tone content. Thus, the most effective way for screen content coding (SCC) is to use two essentially different coders: a dictionary-entropy coder and a traditional hybrid coder. Although screen content is originally in a full-chroma (e.g., YUV444) format, the current method of compression is to first subsample chroma of pictures and then compress pictures using a chroma-subsampled (e.g., YUV420) coder. Using two chroma-subsampled coders cannot achieve high-quality SCC, but using two full-chroma coders is overkill and inefficient for SCC. To solve the dilemma, this paper proposes a mixed chroma sampling-rate approach for SCC. An original full-chroma input macroblock (coding unit) or its prediction residual is chroma-subsampled. One full-chroma base coder and one chroma-subsampled base coder are used simultaneously to code the original and the chroma-subsampled macroblock, respectively. The coder minimizing rate-distortion (R-D) is selected as the final coder for the macroblock. The two base coders are coherently unified and optimized to get the best overall coding performance and share coding components and resources as much as possible. The approach achieves very high visual quality with minimal computing complexity increment for SCC, and has better R-D performance than two full-chroma coders approach, especially in low bitrate.